2023
DOI: 10.21608/ajfm.2023.281729
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Curcumin Against Monosodium Glutamate-Induced Oxidative Renal Damage: biochemical and histopathological study Received in original form: 23 September 2022 Accepted finally: 5 December 2022

Abstract: Introduction: Monosodium glutamate (MSG) is frequently used as a flavoring agent and taste enhancer in processed modern foods. Aim of study: to assess the effects of MSG on the renal cortex and renal indices of rats and to investigate the possible protective effect of curcumin (biochemically, histologically and immunohistochemically). Material and methodology: for this study, 40 adult male albino rats (10 in each group) were used, first group (control) was given 2 ml / kg olive oil, second group received 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In another study, MSG treated rats showed disorganized renal structure; shrunken glomerular tufts with dilatation of the capsular space, vacuolated cytoplasm of tubular cells with periglomerular fibrosis and interstitial nephritis. [31,32].…”
Section: Groups (N=7) Fpg (Mmol/l) Fpi (Mu/l) Homa-irmentioning
confidence: 99%
“…In another study, MSG treated rats showed disorganized renal structure; shrunken glomerular tufts with dilatation of the capsular space, vacuolated cytoplasm of tubular cells with periglomerular fibrosis and interstitial nephritis. [31,32].…”
Section: Groups (N=7) Fpg (Mmol/l) Fpi (Mu/l) Homa-irmentioning
confidence: 99%